Premature Ejaculation and Utilization of Cognitive Techniques - Serkan AKKOYUNLU; M. Hakan TÜRKÇAPAR; Canan AKKOYUNLU (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
Introduction: Premature ejaculation is the most common male sexual dysfunction leading to distress in many couples. Master and Johnson emphasized the concept of early learned experiences and Kaplan emphasized lack of sensory awareness. For treatment sex therapists mainly utilize start-stop and squeeze techniques as homework. Couples enter sex therapy with some cognitive distortions and beliefs about sex and sexuality. These beliefs are also named sexual myths. For some couples using techniques to challenge cognitive distortions and maladaptive beliefs about sex and sexuality can be used. In this paper by presenting a case we discussed how cognitive techniques can be used along with behaviour techniques with couples. Case: Presenting clients are five years married couple who are thirty and twenty nine years old respectively. They attended to the outpatient clinic with the request of the female client. Their main complaint was premature ejaculation. They were diagnosed premature ejaculation using clinical interview. In treatment besides start and stop technique, cognitive techniques were utilized to address dysfunctional beliefs about sexuality. Discussion: Premature ejaculation is a male sexual dysfunction that causes distress and intimacy problems between couples. Stop start and squeeze techniques were accepted as the choice of treatment but their effectiveness is questioned recently. Also cognitive distortions and maladaptive beliefs may hamper therapy progress. Besides that, behavioral techniques utilizing cognitive techniques to lessen the degree of dysfunctional beliefs about sex and sexuality may help the couple to overcome premature ejaculation and enhance sexual satisfaction and intimacy.